(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Статтю присвячено проблемі активізації навчальної діяльності студентів вищих педагогічних закладів. Автор розглядає інтерактивне навчання як засіб формування пізнавальної активності. Ключові слова: інтерактивне навчання, активізація, засіб, пізнавальна активність. The article is devoted to the activation problem of students’ learning activity in the High Pedagogical School. The author considers interactive learning as means of cognitive activity forming. Key words: interactive learning, activation, means, cognitive activity.